The Effect of Sensory Marketing on Roti’O Consumers’ Purchase Decisions at Surabaya City Train - Lathifah, Aisyatul; Andarini, Sonja (Jurnal Sains Sosio Humaniora, 2026)
Fierce competition in the bread industry has prompted companies to implement sensory-based marketing strategies to influence consumer purchasing decisions. This study aims to analyze the influence of sensory-based marketing which includes aroma, taste, and visual on purchasing decisions for Roti’O products. The method used in this study was a quantitative approach involving a survey in which questionnaires were distributed to 196 respondents who had previously purchased Roti’O products at the Gubeng Station, Pasarturi Station, and Wonokromo Station outlets in Surabaya. Sampling was conducted using purposive sampling, while data analysis was performed using multiple linear regression analysis with IBM SPSS Statistics 27. The results indicate that, overall, aroma, taste, and visual elements have a significant influence on purchasing decisions. Individually, the aroma and taste variables have a positive and significant influence on purchasing decisions, whereas the visual variable does not have a significant influence on purchasing decisions. The coefficient of determination (R²) value of 0.517 indicates that 51.7% of purchasing decisions can be explained by the aroma, taste, and visual variables, while the remaining 48.3% are influenced by other variables outside the scope of this study. This means that aroma and taste are the main variables influencing consumers’ purchasing decisions regarding Roti’O products, while visual has not yet become a major factor in driving purchasing decisions.